Effects of concentration polarization, temperature and pressure on ultrasound detection of inorganic fouling and cleaning in a spiral-wound membrane module - Chai, G. Y. (2013)
Ultrasonic time-domain reflectometry (UTDR) involves passing an acoustic wave through a medium and analyzing the reflected waveform. In this study, UTDR is used to track the waveform peaks reflected from the outer and inner membranes in the outermost feed channel in a Koch 2521 spiral-wound module. The UTDR amplitude is shown to be more sensitive to fouling than the transit (arrival) time. The local (point) measurement provided by UTDR is shown to be advantageous since its location can be optimized for early fouling detection. Concentration polarization is shown not to compromise UTDR. This is an advantage relative to flux decline that responds to both fouling and concentration polarization. The UTDR amplitude is found to increase with increasing temperature and decreasing pressure. This is explained by the effect these parameters have on the crystallization rate that changes the fouling layer morphology and thereby the reflected UTDR waveform. This study underscores the importance of establishing a UTDR reference surface suitable for unambiguous detection of fouling. It also emphasizes the necessity for good temperature and pressure control during UTDR measurements as well as a more comprehensive understanding of the effects of operating condition changes on the ultrasound waveforms.